단파장자외선/TiO2 공정에 의한 가스상 톨루엔의 분해 및 습식세정장치에 의한 분해생성물의 제거 - 정주영; 정종수 (한국환경과학회, 2007)
The photodegradation and by-products of the gaseous toluene with TiO2 (P25) and short-wavelength UV (UV254+185nm) radiation were studied. The toluene was decomposed and mineralized efficiently owed to the synergistic effect of photochemical oxidation in the gas phase and photocatalytic oxidation on the TiO2 surface. The toluene by the UV254+185nm photoirradiated TiO2 were mainly mineralized CO2 and CO, but some water-soluble organic intermediates were also formed under severe reaction conditions. The ozone and secondary organic aerosol were produced as undesirable by-products. It was found that wet scrubber was useful as post-treatment to remove water-soluble organic intermediates. Excess ozone could be easily removed by means of a MnO2 ozone-decomposition catalyst. It was also observed that the MnO2 catalyst could decompose organic compounds by using oxygen reactive species formed in process of ozone decomposition.